2022
DOI: 10.1029/2022jg006943
|View full text |Cite
|
Sign up to set email alerts
|

Methane and Carbon Dioxide Fluxes in a Temperate Tidal Salt Marsh: Comparisons Between Plot and Ecosystem Measurements

Abstract: Tidal wetlands occupy a fraction of terrestrial land cover yet play an important role in global carbon cycling by serving as regional biogeochemical hotspots. The high magnitude of net primary productivity and positioning at the terrestrial-aquatic interface supports open transfers and transformation of energy and mass across system boundaries (Al-Haj & Fulweiler, 2020;Cai, 2011), while biogeochemical conditions of the sediments slows re-oxidation and vertical release of CH 4 and CO 2 (Alongi, 2020;Emery et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 129 publications
(171 reference statements)
0
21
0
Order By: Relevance
“…Our results require confirmation using site‐specific nutrient manipulation experiments and testing across different saltmarshes. A further challenge relates with the partition method used to derive F A from NEE, where the standardized approaches (e.g., Reichstein et al., 2005) do not consider the influence of key biophysical variables (i.e., tidal fluctuations and soil biogeochemistry) that may locally influence F A in these coastal ecosystems (Hill & Vargas, 2022; Vázquez‐Lule & Vargas, 2021). We also recognize the need for improving spatially implicit assessments of the spatial variability of F A considering uncertainties associated with micrometeorology (Hill et al., 2017; Tuovinen et al., 2019) and structural differences (e.g., vegetation types, water channels, and ecosystem scale) within salt marshes (Trifunovic et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results require confirmation using site‐specific nutrient manipulation experiments and testing across different saltmarshes. A further challenge relates with the partition method used to derive F A from NEE, where the standardized approaches (e.g., Reichstein et al., 2005) do not consider the influence of key biophysical variables (i.e., tidal fluctuations and soil biogeochemistry) that may locally influence F A in these coastal ecosystems (Hill & Vargas, 2022; Vázquez‐Lule & Vargas, 2021). We also recognize the need for improving spatially implicit assessments of the spatial variability of F A considering uncertainties associated with micrometeorology (Hill et al., 2017; Tuovinen et al., 2019) and structural differences (e.g., vegetation types, water channels, and ecosystem scale) within salt marshes (Trifunovic et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…After we assigned F A estimations to a vegetation category, we gap filled each F A time series using the marginal distribution sampling technique with global radiation, soil temperature, air temperature, water dissolve oxygen, and water flux as covariates in “ReddyProc” R package (Wutzler et al., 2018). We selected these independent variables for gap filling because of their high explanatory power for NEE variability as discussed in previous studies at this research site (Hill & Vargas, 2022; Trifunovic et al., 2020; Vázquez‐Lule & Vargas, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…(2022). For comparing to top‐down measurements, such as flux towers to satellites, source areas and (non‐)linearities in downscaling need to be taken into account, whether that is for carbon emissions in a salt marsh (Hill & Vargas, 2022), hotspots of methane in eddy covariance flux tower footprints (Rey‐Sanchez et al., 2022), or land surface temperature over heterogeneous landscapes (Desai, Khan, et al., 2021).…”
Section: A Scale For All Silosmentioning
confidence: 99%
“…Levy et al (2022) reviewed the key challenges for upscaling when it comes to the UK greenhouse gas program and finds an essential role for uncertainty propagation, a factor also evaluated for gross primary productivity upscaling by Xie et al (2022). For comparing to top-down measurements, such as flux towers to satellites, source areas and (non-)linearities in downscaling need to be taken into account, whether that is for carbon emissions in a salt marsh (Hill & Vargas, 2022), hotspots of methane in eddy covariance flux tower footprints (Rey-Sanchez et al, 2022), or land surface temperature over heterogeneous landscapes (Desai, Khan, et al, 2021).…”
Section: A Scale For All Silosmentioning
confidence: 99%
“…A few studies have demonstrated the potential and benefits of utilizing both techniques in heterogeneous wetland ecosystems (Hill & Vargas, 2022; Rey‐Sanchez et al., 2018; Schäfer et al., 2014). Cross‐scale measurements have improved the quantification of CO 2 and CH 4 exchange in several wetland studies (Acosta et al., 2019; Morin et al., 2017; Rey‐Sanchez et al., 2018; Schrier‐Uijl et al., 2010), but have been rarely applied in tidal wetland ecosystems (Hill & Vargas, 2022; Krauss et al., 2016).…”
Section: Introductionmentioning
confidence: 99%